Aplicação industrial de controladores lógicos programáveis, interfaces homem máquina e computadores industriais Bosch Rexroth - Andrade, Willian Jeferson (2013)
This academic work presents an applied scientific research directed to detail the technical aspects of programmable logic controllers, human machine interfaces and industrial computers from German company, Bosch Rexroth. Its main objective is to make a breakdown of key features, functionality, advantages and disadvantages and also the main applications and products based on the information available in the manuals of the manufacturer, which can be found at the website of the company. This also presents a comparison of the most relevant features regarding to other manufacturers in the industry. It briefly describes the software platform used to program the controllers and industrial computers, showing forms of programming and how it is adapted to international standards. Supplemented by a field work, shows the successful application of a set of equipment described in this study, demonstrating a practical efficiency and product functionality.